Macromolecular surfactants synthesized by lipase-catalyzed transesterification of dextran with vinyl decanoate - Kulthida Kaewprapan (2018)
Dextran, a neutral bacterial polysaccharide consisting in glucose units linked in α-1,6 was modified by covalent attachment of linear aliphatic hydrocarbon groups via the formation of ester links. Transesterification reaction between dextran and vinyl dodecanoate was carried out in a polar organic solvent (dimethylsulfoxide) and catalyzed by lipase. Modified dextrans were fractionated using solvents of increasing polarity (ethyl acetate, methanol and water). Except for very low amounts of enzyme, modified polymers covered a range of degrees of substitution (ca. from 10 to 150%, defined as the molar ratio of formed ester bonds to available glucose units) with distribution depending on the initial amounts of reactants and lipase. Soluble fractions recovered at each step exhibited increasing degrees of substitution when decreasing solvent polarity (from water to methanol and ethyl acetate). In comparison, modified dextrans prepared by uncatalyzed transesterification (even over much longer times) exhibited degrees of substitution lower than 15% covering narrower ranges. The adsorption of modified dextrans at oil/water and air/water interface was examined by surface pressure and interfacial tension measurements for degrees of substitution varying from 10 to 150%. © 2011 Elsevier Ltd All rights reserved.